Stochastic processes in networks of queues with exponential service times and only one class of customers - Ferreira, M. A. M. (Applied Mathematical Sciences, 2014)
Two networks of queues models, presented initially by Jackson, in the open case, and Gordon and Newell, in the closed case, stochastic processes are presented and studied in some of their details and problems. The service times are exponentially distributed and there is only one class of customers.